CPT symmetry tests with cold p¯ and antihydrogen. Issue 7 (4th June 2013) - Yamazaki, Yasunori; Ulmer, Stefan; Blaum, Klaus; Müller, Holger; Severijns, Nathal
<x xml:space="preserve">Abstract</x> Precision comparisons of the properties of particles and their corresponding antiparticles are highly relevant because the Standard Model of elementary particle physics, a local, Lorentz‐invariant field theory, is necessarily symmetric with respect to the combined CPT operation. This symmetry defines exact equality between the fundamental properties of particles and their anti‐images. Any measured and confirmed violation constitutes a significant challenge to the Standard Model. Recent results of different CPT‐tests are summarized, with emphasis to the high‐precision measurement of the magnetic moment of the proton and the antiproton, as well as the precision investigation of antihydrogen ground state hyperfine splitting.